Climate-Induced Tree Senescence Leads to a Transient Increase in Reproductive Success of a Large Woodpecker Species - Vergara-Egert, P; Fierro-Tapia, C; Alaniz-Baeza, A; Carvajal-Leon, M (Elsevier B.V., 2022)
Climate change-induced mortality of trees is a concerning phenomenon for global forest ecosystems. The rapid decay and death of long-lived trees can significantly impact forest dynamics, with effects that transmit through ecological networks, becoming more evident in organisms occupying high trophic levels, such as large and specialized woodpecker species. However, understanding how populations of high trophic level species respond to climate change is still a challenge. In this study it was analyzed 32-year data of social groups of the Magellanic Woodpecker (Campephilus magellanicus) in North Patagonia, a region facing increasingly frequent droughts and increased temperatures. A positive trend in the size of woodpecker social groups as a response to climate-induced tree senescence was tested. A causal structural equation model examining climate- tree senescence- woodpecker relationships was used. Increasing nonlinear trends and positive interannual growth rates (>10%) for tree senescence and group size were found. Lowland forest sites had higher levels of tree senescence and more numerous social groups. The causal model supported the positive effect of mean temperature on tree senescence and the positive association of woodpeckers with tree senescence. These results provide evidence of a climate-induced increase in tree senescence that causes an increase in the size of woodpecker social groups. It is suggested that accelerated decay and mortality of trees in the northern Patagonian forests will decrease the stocks of deadwood in the long term, threatening the persistence of this large woodpecker species. © 2021 Elsevier B.V.